Identification of germline genetic mutations in patients with pancreatic cancer. Issue 24 (6th October 2015) - Salo‐Mullen, Erin E.; O'Reilly, Eileen M.; Kelsen, David P.; Ashraf, Asad M.; Lowery, Maeve A.; Yu, Kenneth H.; Reidy, Diane L.; Epstein, Andrew S.; Lincoln, Anne; Saldia, Amethyst; Jacobs, Lauren M.; Rau‐Murthy, Rohini; et al.
Abstract : BACKGROUND: Pancreatic adenocarcinoma (PAC) is part of several cancer predisposition syndromes; however, indications for genetic counseling/testing are not well‐defined. In the current study, the authors sought to determine mutation prevalence and characteristics that are predictive of an inherited predisposition for PAC. METHODS: A total of 175 consecutive patients with PAC who underwent clinical genetics assessment at Memorial Sloan Kettering Cancer Center between 2011 and 2014 were identified. Clinical data, family history, and germline results were evaluated. RESULTS: Among 159 patients with PAC who pursued genetic testing, 24 pathogenic mutations were identified (15.1%; 95% confidence interval, 9.5%‐20.7%), including BRCA2 (13 mutations), BRCA1 (4 mutations), p16 (2 mutations), PALB2 (1 mutation), and Lynch syndrome (4 mutations). BRCA1 / BRCA2 prevalence was 13.7% in Ashkenazi Jewish (AJ) patients (95 patients) and 7.1% in non‐AJ patients (56 patients). In AJ patients with a strong, weak, or absent family history of BRCA ‐associated cancers, the mutation prevalence was 16.7%, 15.8%, and 7.4%, respectively. The mean age at the time of diagnosis in all mutation carriers was 58.5 years (range, 45‐75 years) compared with 64 years (range, 27‐87 years) in those not carrying a mutation ( P =  .02). Although BRCA2 was the most common mutation identified, no patients with early‐onset PAC (diagnosed at age ≤ 50 years) harbored a BRCA2 mutation and the mean age at diagnosis in BRCA2 carriers was equivalent to that of individuals who were not mutation carriers ( P =  .34). Mutation prevalence in patients with early‐onset disease (21 patients) was 28.6%, including BRCA1 (2 mutations), p16 (2 mutations), MSH2 (1 mutation), and MLH1 (1 mutation). CONCLUSIONS: Mutations in BRCA2 account for > 50% of patients with PAC with an identified susceptibility syndrome. AJ patients were found to have high BRCA1 / BRCA2 prevalence regardless of personal/family history, suggesting that ancestry alone indicates a need for genetic evaluation. With the exception of BRCA2 ‐associated PAC, an inherited predisposition for PAC is associated with an earlier age at PAC diagnosis, suggesting that this subset of patients may also represent a population warranting further evaluation. Cancer 2015;121:4382–8. © 2015 American Cancer Society . Abstract : In a consecutive series of patients with pancreatic adenocarcinoma undergoing genetic cancer risk assessment, a mutation prevalence of 15.1% was identified, with BRCA2 mutations being the most common. Patients with pancreatic adenocarcinoma who are of Ashkenazi Jewish ancestry, irrespective of family cancer history, or those with an early age at the time of diagnosis may warrant genetic cancer risk assessment.